Macrophage-inherited exosome excise tumor immunosuppression to expedite immune-activated ferroptosis - Yan Liu; Junjie Liu; Qin Wang; Kun Zhang; Chunyan Zhu; Duo Wang; Guanhua Qiu; Xiaoqi Zhu; Chao Fang (Journal for ImmunoTherapy of Cancer)
Background Immunosuppressive tumor microenvironment (ITM) remains an obstacle that jeopardizes clinical immunotherapy.Methods To address this concern, we have engineered an exosome inherited from M1-pheototype macrophages, which thereby retain functions and ingredients of the parent M1-phenotype macrophages. The delivered RSL3 that serves as a common ferroptosis inducer can reduce the levels of ferroptosis hallmarkers (eg, glutathione and glutathione peroxidase 4), break the redox homeostasis to magnify oxidative stress accumulation, promote the expression of ferroptosis-related proteins, and induce robust ferroptosis of tumor cells, accompanied with which systematic immune response activation can bbe realized. M1 macrophage-derived exosomes can inherit more functions and genetic substances than nanovesicles since nanovesicles inevitably suffer from substance and function loss caused by extrusion-arised structural damage.Results Inspired by it, spontaneous homing to tumor and M2-like macrophage polarization into M1-like ones are attained, which not only significantly magnify oxidative stress but also mitigate ITM including M2-like macrophage polarization and regulatory T cell decrease, and regulate death pathways.Conclusions All these actions accomplish a synergistic antitumor enhancement against tumor progression, thus paving a general route to mitigate ITM, activate immune responses, and magnify ferroptosis.